2014
DOI: 10.1016/j.sbspro.2014.05.161
|View full text |Cite
|
Sign up to set email alerts
|

Macrolinguistic Errors in Arab EFL Learners’ Essays

Abstract: This study attempts to identify the errors that Arab EFL learners commit in writing English essays at the macrolinguistic level. It also tries to determine the causes of these problems and propose remedial strategies. More specifically stated the study seeks answers to the following questions: (1) What errors do Arab learners of English commit in writing English essays at the pragmatic and discoursal levels? (2) What are the possible causes of these errors? (3) How can such problems be minimized? and (4) To wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 4 publications
1
7
0
Order By: Relevance
“…In addition, Arab learners have a major macro-linguistics failure when it comes to writing, due to different reasons such as unqualified teachers, inadequate teaching practice, and insufficient exposure to authentic texts in English (Fareh, 2014). Two major studies in particular, were conducted to investigate the influence of using language-learning strategies to improve the writing skills of Saudi EFL students.…”
Section: Teaching Strategiesmentioning
confidence: 99%
“…In addition, Arab learners have a major macro-linguistics failure when it comes to writing, due to different reasons such as unqualified teachers, inadequate teaching practice, and insufficient exposure to authentic texts in English (Fareh, 2014). Two major studies in particular, were conducted to investigate the influence of using language-learning strategies to improve the writing skills of Saudi EFL students.…”
Section: Teaching Strategiesmentioning
confidence: 99%
“…These pedagogical practices may help students develop their grammatical competence rather than communicative or discourse competence. In this respect, Fareh (2014b) holds that:…”
Section: Objectives Of the Studymentioning
confidence: 99%
“…The results to items (1 & 2) agree with Sharawneh (2012) who found that the assessment of the writing ability among language teachers and students has always been important because the results of such an evaluation are used for a variety of administrative, instructional and research purposes. Teachers use these results to help improve, influence, refine and shape their students' attained writing ability, and Fareh (2014) who found that social media has several effects on academic work.…”
Section: 12mentioning
confidence: 99%
“…Social media includes activities such as socializing and networking online through words, pictures and videos. Also, it is redefining how it is related to teach other as humans and how humans relate to the organizations that serve us, (Murad & Khalil, 2015;Fareh, 2014) stated that students learn more in less time when they receive computer-based instruction and the use of technology in higher level reasoning and problem-solving abilities. Harmer (2004) found that one of the positive influences is that the internet plays a vital role in providing teenagers with multi-connected networks across the globe.…”
Section: Introduction and Theoretical Background 211 Part One: Related Literaturementioning
confidence: 99%